Scaphoid Nonunions Treated with Nonvascularized Bone Grafting and Screw Fixation - Zondervan, Robert L.; Childe, Jessica R.; Kustasz, Robin; Hornbach, Erich E. (Journal of Wrist Surgery, 2023)
Background Vascularized bone grafting with screw fixation is currently considered the treatment of choice for scaphoid nonunions with avascular necrosis (AVN) of the proximal pole. A viable alternative to using vascularized bone grafts for scaphoid nonunions with AVN is nonvascularized bone grafting with screw fixation.Question What are the functional outcomes of patients with scaphoid nonunions and associated proximal pole AVN who are treated with nonvascularized distal radius bone grafting and screw fixation?Patients and Methods Eight scaphoid nonunions with AVN, which received nonvascularized distal radius bone graft and screw fixation, underwent a retrospective review. Range of motion, strength, and Disabilities of the Arm, Shoulder, and Hand (DASH) scores were obtained. Follow-up X-rays were compared with immediate postoperative X-rays.Results At a mean follow-up of 88.9 months, thumb palmar abduction and radial abduction were significantly higher on the operative side (p = 0.28 and 0.49, respectively). Extension/flexion arc was significantly lower in the operative wrist (p = 0.148). There was no significant difference between the operative and nonoperative sides with regard to strength. The median postoperative DASH score was 2.9 (interquartile range [IQR]: 8.3). There was no progression of osteoarthritis when immediate postoperative and follow-up X-rays were compared. Radiographic union was observed in six of the seven (85.7%) patients who were able to return to the office for follow-up radiographs. The mean scapholunate and radioscaphoid angles measured on X-rays were within normal anatomic range postoperatively.Conclusions Using nonvascularized distal radius bone graft and screw fixation in the treatment of scaphoid nonunions with associated AVN has favorable radiologic and functional outcomes and should be considered a viable treatment option for this difficult problem.
Keywords: scaphoid; fracture; AVN; avascular necrosis; wrist; graft